Quasi-two-dimensional perovskite containing double-anchor-group cross-linking agent and preparation method of quasi-two-dimensional perovskite
By using a double-anchor-based crosslinking agent in perovskite solar cells, anchoring the nickel oxide surface and promoting the vertical growth of the perovskite layer, the problems of low efficiency and insufficient stability of the quasi-two-dimensional perovskite solar cell are solved, and the problem of low efficiency and insufficient stability of the quasi-two-dimensional perovskite solar cell is achieved. Higher photovoltaic performance and stability.
Patent Information
- Application Number
- CN202411363860.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-01-03
AI Technical Summary
Quasi-two-dimensional perovskite solar cells have low efficiency and insufficient stability, mainly due to the low energy transfer efficiency caused by the van der Waals gap between the perovskite layers, which limits its photovoltaic performance.
The double-anchor crosslinking agent, including 4-(aminomethyl)benzoic acid and other crosslinking agents, combined with the perovskite system and precursor solution, anchor the surface of nickel oxide through carboxylic functional groups to form hydrogen bonds or electrostatic interactions. Promote the vertical growth and coupling of perovskite layers and reduce the Van der Waals gap.
It improves the light and thermal stability of the perovskite film, enhances the carrier transmission performance, and improves the efficiency and stability of the perovskite solar module.
Smart Images

Figure CN119255689A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to perovskite battery material technology, and in particular to a quasi-two-dimensional perovskite containing a double-anchor crosslinking agent and a preparation method thereof. Background Art
[0002] Perovskite solar cells (PSCs) are solar cells that use perovskite-type organic metal halide semiconductors as light-absorbing materials. The core material is a perovskite semiconductor. Perovskite solar cells are considered a promising photovoltaic technology due to their high power conversion efficiency (PCE) and low manufacturing cost.
[0003] However, this photovoltaic technology still faces bottlenecks such as low efficiency and insufficient stability of large-area perovskite solar modules (PSMs), which seriously restrict its large-scale commercial application. Compared with three-dimensional perovskites, quasi-2D perovskites are more resistant to environmental conditions (humidity, oxygen) and show stronger thermal and photochemical stability. However, the van der Waals gap between the quasi-2D perovskite layers also leads to low energy transfer efficiency in the perovskite film, limiting the photovoltaic performance of PSCs. Therefore, reducing the van der Waals gap between the quasi-2D perovskite layers and enhancing the interaction between adjacent spacer layers are crucial to improving the efficiency and stability of quasi-2D perovskites and PSMs. Summary of the invention
[0004] The purpose of the present invention is to provide a quasi-two-dimensional perovskite containing a double anchor crosslinker and a preparation method thereof, so as to solve the above-mentioned deficiencies in the prior art.
[0005] In order to achieve the above-mentioned purpose, the present invention provides the following technical solution: a quasi-two-dimensional perovskite containing a double anchor crosslinker, wherein the raw materials of the quasi-two-dimensional perovskite containing a double anchor crosslinker include: a double anchor crosslinker, a perovskite system and a precursor solution.
[0006] Further, the double anchor crosslinking agent includes a combination of at least one crosslinking agent selected from 4-(aminomethyl)benzoic acid, 3-(aminomethyl)benzoic acid, 2-(aminomethyl)benzoic acid, 4-(aminomethyl)benzenesulfonic acid, 3-(aminomethyl)benzenesulfonic acid or 2-(aminomethyl)benzenesulfonic acid.
[0007] Furthermore, the perovskite system is BA2(FA 0.85 Cs 0.15 ) n-1 Pb n I 3n+1 (n = positive integer) or BA2FA n- 1Pbn I 3n+1 (n=positive integer).
[0008] Furthermore, the precursor solution is prepared by dissolving 1.0 mmol of the perovskite system in 1 ml of a mixed solvent system, and the mixing ratio of the mixed solvent system is DMF:NMP:2-Me=7:3-x:x (0≤x≤3).
[0009] Furthermore, the content of the double anchor crosslinking agent is 1% to 4% by mole relative to the PbI2 in the precursor solution.
[0010] A method for preparing a quasi-two-dimensional perovskite containing a double anchor crosslinker comprises the following steps:
[0011] A double anchor crosslinker is added to the precursor solution, and the mixture is mixed and stirred until fully dissolved to obtain a quasi-two-dimensional perovskite containing the double anchor crosslinker.
[0012] A perovskite solar module comprises a quasi-two-dimensional perovskite containing a double anchor crosslinking agent, a transparent conductive oxide substrate, an inorganic p-type semiconductor hole transport layer, an electron transport layer, a barrier layer and an electrode layer, an organic encapsulation layer and a cover glass.
[0013] Furthermore, the inorganic p-type semiconductor hole transport layer material is nickel oxide or metal-doped nickel oxide.
[0014] Furthermore, the barrier layer is bathoxime BCP or tin oxide.
[0015] Furthermore, the electrode layer is a metal electrode, and the metal electrode is a combination of at least one metal electrode selected from the group consisting of silver, gold, copper, bismuth, chromium, and nickel.
[0016] Compared with the prior art, the quasi-two-dimensional perovskite containing a double anchor crosslinker and a preparation method thereof provided by the present invention reduces the van der Waals gap between adjacent spaced perovskite layers by introducing double anchor crosslinker molecules, promotes the interlayer coupling of the quasi-two-dimensional perovskite, and thus improves the light and thermal stability of the perovskite film;
[0017] The carboxyl functional group (-COOH) in the double-anchor cross-linker molecule can be anchored on the surface of nickel oxide to passivate the surface defects of nickel oxide. The double-anchor cross-linker molecule anchored on the surface of nickel oxide forms hydrogen bonds or electrostatic interactions with the perovskite Pb-I framework through the -NH2 functional group. In the process of coating the quasi-two-dimensional perovskite film, it induces the vertically oriented growth of low-dimensional perovskite with a high-purity phase, improves the carrier transport performance, and increases the stability of the perovskite solar module. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can also be obtained based on these drawings.
[0019] Figure 1 A schematic diagram of the structure of a perovskite solar module provided in an embodiment of the present invention;
[0020] Figure 2 A schematic diagram of a perovskite coordination model and its charge density distribution calculated by functional density theory (DFT) provided in an embodiment of the present invention;
[0021] Figure 3 The nickel oxide (NiO) based on different treatments provided in the embodiment of the present invention x ) of N1 s Schematic diagram of X-ray photoelectron spectroscopy;
[0022] Figure 4 A schematic diagram of an X-ray photoelectron spectrum provided by an embodiment of the present invention;
[0023] Figure 5 A SEM schematic diagram of a perovskite film provided in an embodiment of the present invention;
[0024] Figure 6 A schematic diagram of in-situ PL spectrum monitoring results of 4-ABA-free and 4-ABA-containing perovskite films provided in an embodiment of the present invention after continuous laser irradiation for 0 to 10 hours in ambient air;
[0025] Figure 7 A schematic diagram of in-situ variable temperature XRD of perovskite provided in an embodiment of the present invention;
[0026] Figure 8 A schematic diagram of the aging and photothermal stability test of a perovskite solar module provided in an embodiment of the present invention;
[0027] Fig. 9 A schematic diagram of a stability test of a perovskite solar module provided in an embodiment of the present invention;
[0028] Fig.10 The present invention provides structural diagrams P1 to P3 during the preparation of a perovskite solar module. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings.
[0030] Embodiment 1:
[0031] A quasi-two-dimensional perovskite containing a double-anchor crosslinker. The raw materials of the quasi-two-dimensional perovskite containing a double-anchor crosslinker include: a double-anchor crosslinker, a perovskite system and a precursor solution.
[0032] The double anchor crosslinker includes a combination of at least one of 4-(aminomethyl)benzoic acid (4-ABA), 3-(aminomethyl)benzoic acid, 2-(aminomethyl)benzoic acid, 4-(aminomethyl)benzenesulfonic acid, 3-(aminomethyl)benzenesulfonic acid or 2-(aminomethyl)benzenesulfonic acid. The structural formulas of 4-(aminomethyl)benzoic acid, 3-(aminomethyl)benzoic acid, 2-(aminomethyl)benzoic acid, 4-(aminomethyl)benzenesulfonic acid, 3-(aminomethyl)benzenesulfonic acid and 2-(aminomethyl)benzenesulfonic acid are as follows:
[0033] The strong interaction between -COOH and -NH2 in the 4-ABA double anchor crosslinker and the perovskite can reduce the van der Waals gap between adjacent spaced perovskite layers and promote the coupling between quasi-two-dimensional perovskite layers. At the same time, 4-ABA can be anchored on the surface of nickel oxide to form a self-assembled molecular monolayer. In the process of coating and preparing quasi-two-dimensional perovskite films, it induces the vertically oriented growth of low-dimensional perovskites with high purity phases and improves the carrier transport characteristics. The double anchor crosslinker based on the present invention can effectively solve the problems of low efficiency and insufficient stability of quasi-two-dimensional perovskite solar modules.
[0034] The perovskite system is BA2(FA 0.85 Cs 0.15 ) n-1 Pb n I 3n+1 (n = positive integer) or BA2FA n-1 Pb n I 3n+1 (n=positive integer).
[0035] The precursor solution is prepared by dissolving 1.0 mmol perovskite system in 1 ml mixed solvent system, and the mixing ratio of the mixed solvent system is DMF: NMP: 2-Me = 7: 3-x: x (0≤x≤3). The addition of 2-ME is of great significance for promoting the rapid and uniform crystallization of perovskite in the vacuum flash memory process.
[0036] The content of the double anchor crosslinking agent is 1% to 4% by mole relative to the Pb I2 in the precursor solution.
[0037] Embodiment 2:
[0038] This embodiment provides a technical solution based on the first embodiment: a method for preparing a quasi-two-dimensional perovskite containing a double anchor crosslinker, comprising the following steps: adding a double anchor crosslinker to a precursor solution, and mixing and stirring until fully dissolved to obtain a quasi-two-dimensional perovskite containing a double anchor crosslinker.
[0039] The specific implementation method is to select the perovskite system BA2 (FA 0.85 Cs 0.15 ) n-1 Pb n I 3n+1 , solvent system DMF:NMP:2-Me=7:2.5:0.5.
[0040] First, 700 μL DMF, 250 μL NMP and 50 μL 2-Me were measured and mixed to obtain a solvent system; 0.035 g Cs I, 0.0447 g BAI, 0.13 g FAI, 0.461 g Pb I2 and 1% to 4% 4-ABA (relative to the molar percentage of Pb I2) were weighed in sequence using an electronic analytical balance and dissolved in the solvent system; after mixing and stirring until fully dissolved, a quasi-two-dimensional perovskite containing a double anchor crosslinker was obtained for use.
[0041] Then, in an air environment, a perovskite precursor wet film is coated by blade coating or slit coating, and then the calcium wet film is treated by a vacuum flash crystallization device for 40 seconds, and then annealed at 130°C for 30 minutes to obtain a quasi-two-dimensional large-area perovskite film containing a double anchor crosslinker. The blade coating parameters are a coater gap of 100 to 400 μm and a coating speed of 10 mm / s-25 mm / s.
[0042] Embodiment three:
[0043] See also Figure 1 and Fig.10 This embodiment provides a technical solution based on the second embodiment: a perovskite solar module, including a quasi-two-dimensional perovskite containing a double anchor crosslinker, and also including a transparent conductive oxide substrate, an inorganic p-type semiconductor hole transport layer, an electron transport layer, a barrier layer and an electrode layer, an organic encapsulation layer and a cover glass. The inorganic p-type semiconductor hole transport layer material is nickel oxide or metal-doped nickel oxide. The barrier layer is bathoxime BCP or tin oxide. The electrode layer is a metal electrode, and the metal electrode is a combination of at least one metal electrode of silver, gold, copper, bismuth, chromium or nickel, and the electrode thickness is 100nm to 1μm.
[0044] See also Figure 1 The perovskite solar module is configured from bottom to top including a transparent conductive oxide substrate, an inorganic p-type semiconductor hole transport layer, a perovskite active layer, an electron transport layer, a barrier layer, an electrode layer, an organic encapsulation layer and a cover glass.
[0045] The inorganic p-type semiconductor hole transport layer material is nickel oxide or metal-doped nickel oxide, and the doped metal is one or more metals such as lithium and magnesium. The metal-doped nickel oxide preparation method is as follows: nickel acetylacetonate, magnesium acetate tetrahydrate and lithium acetate are added to a mixed solution of 100 mL (volume ratio 95:5) of acetonitrile and ethanol in a molar atomic ratio of Ni:Mg:Li of 80:15:5 to prepare a Ni solution with a total metal ion concentration of 0.02 M. 0.8 Mg 0.15 Li 0.05 O precursor solution; the precursor solution is automatically sprayed on the hot FTO glass (570°C) through an air nozzle. After the spraying is completed, the sample is kept at 570°C for 40 minutes and then naturally cooled to room temperature to obtain metal-doped nickel oxide.
[0046] Bath ketone BCP is prepared by vacuum evaporation coating equipment with a thickness of 1 to 10 nm.
[0047] The preparation process of perovskite solar modules includes the following steps:
[0048] First, a nanosecond green laser was used to etch a transparent conductive oxide substrate (substrate area ≥ 5 cm × 5 cm) to obtain a P1 scribe line; then the substrate was cleaned, an inorganic p-type semiconductor hole transport layer was deposited, a quasi-two-dimensional perovskite active layer containing a double anchor crosslinker was coated, and an electron transport layer and a barrier layer were deposited;
[0049] Then, nanosecond green laser is used to perform P2 etching to form a series channel of adjacent sub-cells. The P2 etching should etch all the film layers above the transparent conductive oxide so that the transparent conductive oxide is completely exposed to form a good ohmic contact at the series interface.
[0050] Then, the metal electrode is deposited, and the substrate with the deposited electrode is subjected to P3 etching. P3 requires that the laser power remain stable during the etching process so that the metal electrode is completely cut off without overlap to prevent short circuits of adjacent sub-cells. The structures of P1 to P3 are as follows: Fig.10 As shown, the number of sub-batteries can be increased or decreased according to the device size design;
[0051] Finally, the module is packaged, the organic packaging material is evenly coated on the electrode layer, covered with a cover glass, and hot-pressed using a laminator to obtain a perovskite solar module.
[0052] Embodiment 4:
[0053] See also Figure 2 This embodiment provides a technical solution based on the second embodiment: functional density theory (DFT) calculation of the perovskite coordination model and its charge density distribution.
[0054] Density Functional Theory (DFT) calculations of quasi-two-dimensional perovskite materials are a powerful tool for understanding and predicting the electronic structure, optical properties, magnetic properties, and other physical and chemical properties of these materials. Figure 2 (a) does not contain 4-ABA; (b) contains 4-ABA.
[0055] Theoretical study reveals the interaction mechanism between 4-ABA organic spacer and quasi-two-dimensional perovskite. Figure 2 a. The calculation results show that 4-ABA can bind to the incompletely coordinated Pb 2+ coordination is formed, while only van der Waals interactions exist between BA cations and the octahedral 3D perovskite layer.
[0056] See also Figure 2 b, After the introduction of 4-ABA, the oxygen atoms and Pb contained in 4-ABA 2+ There is an obvious charge transfer between them, which further verifies the strong interaction between the two. In order to quantitatively study the strength of chemical interaction, the binding energy E between different compounds was calculated by the following formula: b :
[0057] △E b =E A+B -E A -E B
[0058] Where E A+B represents the total energy of the interaction between the perovskite unit cell and the 4-ABA molecule, E A represents the perovskite unit cell energy without 4-ABA molecules, E B Represents the energy of 4-ABA molecules. The calculation results show that the binding energy of the perovskite system without 4-ABA molecules is -5.64eV, while the binding energy of the perovskite system with 4-ABA molecules is -6.29eV. The increase in binding energy proves that there is a stronger interaction between 4-ABA and halide perovskite compared with BA cations, which is consistent with the experimental test results above. The specific values of its binding energy are shown in Table 1.
[0059] Table 1 Binding energy between perovskite and molecules
[0060]
[0061] Embodiment five:
[0062] See also Figure 3-Figure 9This embodiment provides a technical solution based on the third embodiment: testing various properties of the quasi-two-dimensional perovskite and perovskite solar module containing a double anchor crosslinker:
[0063] 1. Nickel oxide (NiO) based on different treatments x ) of N1 s X-ray photoelectron spectroscopy.
[0064] 4-ABA can bind to NiO through the -COO functional group x Surface hydroxyl groups interact and adsorb on NiO x Surface, on NiO x 4-ABA was deposited on the surface, and then rinsed with DMSO, a benign solvent for 4-ABA, to obtain DMSO-rinsed NiO x / 4-ABA; at the same time, NiO without 4-ABA deposition x For comparative example.
[0065] Figure 3 (a) is NiO x and NiO x / 4-ABA; (b) NiO x XPS spectrum of / 4-ABA after the film was washed with DMSO. The inset is the DMSO solution of 4-ABA.
[0066] See also Figure 3 a, NiO without DMSO rinse x The characteristic peak of N1s was observed for 4-ABA, which confirmed the presence of 4-ABA on the surface of NiOx treated with 4-ABA.
[0067] See also Figure 3 b, NiO washed with DMSO x / 4-ABA can still be observed at the N1s peak, indicating that 4-ABA can bind to NiO through the -COOH functional group. x Surface hydroxyl interactions in NiO x A strong chemical adsorption is formed on the surface and is not easily eluted by benign solvents.
[0068] In summary, 4-ABA can be anchored on NiO via -COOH. x The surface is then incorporated into the Pb-I framework through hydrogen bonding or electrostatic interaction with the perovskite via -NH2. This interface modification helps to passivate the interface defects at the buried interface and avoid the interaction between the perovskite and NiO x direct contact between the perovskite / NiO x Potential redox reactions at the interface.
[0069] 2. X-ray photoelectron spectroscopy (XPS) characterization of nickel oxide thin films.
[0070] The present invention further understands that 4-ABA has an effect on NiO x The influence of the interface was studied by XPS characterization method on 4-ABA / NiO x O peak and Ni peak of the film.
[0071] Figure 4 (a) is NiO x Ni 2p X-ray photoelectron spectrum of thin films; (b) NiO x / 4-ABA film Ni 2p X-ray photoelectron spectrum; (c) NiO x X-ray photoelectron spectrum of thin film O1s; (d) NiO x X-ray photoelectron spectrum of O1s of / 4-ABA thin film.
[0072] See also Figure 4 a and Figure 4 b, NiO without DMSO rinse x / 4-ABA thin film Ni 3+ / Ni 2+ The ratio of 4-ABA increased from 2.38 to 3.10, indicating that NiO without DMSO washing x / 4-ABA film has improved conductivity. Figure 4 c and Figure 4 d, NiO without DMSO rinse x The O1s peak intensity of NiOOH in the / 4-ABA film is relatively higher than that of NiO without DMSO rinse. x has decreased, indicating that there are fewer trap states from undercoordinated oxygen atoms.
[0073] The above shows that 4-ABA can not only serve as a dual-anchor crosslinker in the quasi-two-dimensional perovskite bulk phase, but also can self-assemble at the buried interface and serve as a molecular connector at the buried interface to stabilize the hole transport layer / perovskite buried interface and achieve a bottom-up system crosslinking effect.
[0074] 3. Detection of perovskite film morphology and crystal orientation.
[0075] Figure 5 (a) is the morphology of the standard perovskite film; (b) is the morphology of the perovskite film containing 4-ABA; (c) is the GIWAXS two-dimensional image of the standard perovskite film; (d) is the GIWAXS two-dimensional image of the perovskite film containing 4-ABA.
[0076] See also Figure 5a, The perovskite film without 4-ABA has large grain size, but has holes and poor film coverage. This may be because there are fewer nucleation sites and the crystal growth rate is greater than the nucleation rate.
[0077] See also Figure 5 b, SEM of the perovskite film after adding 4-ABA, it can be observed that the grains of the perovskite film become smaller, without pinholes and evenly distributed. The reason for the improvement in the quality of the perovskite film may be that the interaction between 4-ABA and the perovskite precursor inhibits the perovskite crystallization rate. Before the grains become larger, the introduction of 4-ABA can induce more nucleation sites, which helps to form a dense perovskite film.
[0078] See also Figure 5 c and Figure 5 d. To further study the effect of 4-ABA on the orientation of quasi-two-dimensional perovskite crystals, GIWAXS characterization was performed on the perovskite film samples. The diffraction rings of the perovskite film without 4-ABA and the perovskite film containing 4-ABA were compared. The perovskite film containing 4-ABA has dispersed Bragg lattices in the small n value phase. This result shows that the introduction of 4-ABA in the precursor solution can regulate the nucleation and growth of quasi-two-dimensional perovskite crystals and promote the alignment and growth of highly oriented perovskite crystals on the (0k0) plane parallel to the substrate surface.
[0079] 4. Detection of light and thermal stability of perovskite films.
[0080] Figure 6 (a) shows the in-situ PL spectrum monitoring results of the perovskite film without 4-ABA after continuous laser irradiation in ambient air for 0 to 10 hours; (b) shows the in-situ PL spectrum monitoring results of the perovskite film containing 4-ABA after continuous laser irradiation in ambient air for 0 to 10 hours.
[0081] See also Figure 6 a, In-situ steady-state PL spectroscopy is used to monitor the change in PL intensity during the photoaging of perovskite films. During the aging process, the intensity of the perovskite film without 4-ABA decays significantly with the increase of aging time ( Figure 6 a), while the PL intensity of the perovskite film containing 4-ABA did not decay significantly after continuous laser irradiation for 10 h. The above results show that the introduction of 4-ABA into quasi-2D perovskite can effectively improve the photostability of the perovskite film.
[0082] Figure 7(a) is the in-situ temperature-variable XRD pattern of the perovskite film containing 4-ABA; (b) is the in-situ temperature-variable XRD pattern of the perovskite film without 4-ABA; (c) is the local enlarged XRD pattern of the perovskite film containing 4-ABA: Pb I2; (d) is the local enlarged XRD pattern of the perovskite film containing 4-ABA: perovskite; (e) is the local enlarged XRD pattern of the perovskite film without 4-ABA: Pb I2; (f) is the local enlarged XRD pattern of the perovskite film without 4-ABA: perovskite.
[0083] See also Figure 7 , the effect of 4-ABA on the thermal stability of perovskite films was investigated by in-situ variable temperature XRD test, please refer to Figure 7 b and Figure 7 e. When the temperature reaches about 160°C, the perovskite film without 4-ABA shows the characteristic diffraction peak of Pb I2. When the temperature is further increased to about 260°C, the sample is almost completely decomposed into Pb I2. Please refer to Figure 7 a and Figure 7 c. In contrast, when the temperature reaches 210 °C, the 4-ABA-containing perovskite film still shows no obvious degradation, and even when the annealing temperature is further increased to 275 °C, the characteristic diffraction peak of the perovskite remains almost unchanged.
[0084] The above results show that the introduction of 4-ABA can effectively inhibit the thermal decomposition of quasi-two-dimensional perovskite films and improve the thermal stability of the films.
[0085] 5. Device efficiency testing of perovskite modules.
[0086] By adjusting the doping concentration of 4-ABA, it was determined that the device performance of the perovskite solar module with a 4-ABA doping concentration of 2% (relative to the molar ratio of Pb I2 concentration) was the best, with an optimal PCE of 16.05%, corresponding to V OC is 4.125V, I SC The A value is 0.055A, and the FF value is 68.34%. For specific performance parameters of perovskite modules with other concentrations, please refer to Table 2.
[0087] Table 2 Statistics of optimal parameters at different concentrations
[0088]
[0089] The improvement in photovoltaic performance is mainly due to the fact that the introduction of 4-ABA can promote the growth of highly uniform and ordered quasi-two-dimensional perovskite films and promote the Pb-I framework to have a suitable growth orientation relative to the substrate. In particular, the introduction of 4-ABA can promote the growth of perovskite films with preferential crystal orientation, giving them a longer carrier lifetime and more efficient carrier transport, ultimately improving photovoltaic performance.
[0090] Photovoltaic performance mainly refers to the ability of photovoltaic modules or photovoltaic systems to convert solar energy into electrical energy under various conditions and its related characteristics. Open circuit voltage (Voc): When the positive and negative poles of the photovoltaic module are not connected to the load, the voltage between the positive and negative poles of the module is the open circuit voltage; Short circuit current (Isc): When the positive and negative poles of the photovoltaic module are short-circuited, that is, the voltage V=0, the current at this time is the short circuit current; Fill factor (FF): Fill factor is an important parameter for evaluating the output characteristics of the cells used in photovoltaic modules. It is equal to the ratio of the maximum power of the photovoltaic module to the product of the open circuit voltage and the short circuit current. The higher the value of the fill factor, the more rectangular the output characteristics of the cells used are, and the higher the photoelectric conversion efficiency of the battery; Photoelectric conversion efficiency (PCE), it refers to the efficiency of photovoltaic modules in converting light energy into electrical energy. This parameter is one of the key indicators for measuring the performance of photovoltaic modules, and directly determines the electrical energy output that photovoltaic modules can generate under given lighting conditions.
[0091] 6. Device stability testing of perovskite modules.
[0092] The perovskite solar modules (PSMs) of the type involved in the present invention are placed at a temperature of 50°C and a light intensity of 600Wm -2 Aging test is performed under full-spectrum xenon lamp conditions. The purpose of aging test is to evaluate the performance stability of the module under long-term operation and harsh environment. By simulating extreme conditions (such as high temperature and high light intensity), the aging process can be accelerated, so that the change trend of module performance can be observed in a shorter time.
[0093] Figure 8 (a) is the aging test under light and heat conditions, blue represents the laboratory self-test results, the test environment temperature is 50℃, 600W m -2 Xenon lamp with AM1.5G filter; Yellow represents the test result of the third-party authority VDE, the test conditions are ambient temperature 50℃, 600W m -2 (a) is the photothermal stability of the device with and without 4-ABA after irradiation by a solar simulator; (b) is the laboratory self-test comparing the photothermal stability of the device with and without 4-ABA.
[0094] See also Figure 8 a and Figure 8 b, After aging for 6000 hours, the perovskite solar module containing 4-ABA crosslinker can still maintain 100% of its initial efficiency. In contrast, the perovskite solar module without 4-ABA crosslinker only maintains 78% of its initial efficiency after aging.
[0095] In addition, the PSMs were tested for their wet heat stability under double 85 conditions. Fig. 9(a) is a stability test under dual 85 conditions, blue represents self-test, and yellow represents the test results of the third-party authoritative organization VDE; (b) is a laboratory self-test comparing the wet-heat stability of devices with and without 4-ABA.
[0096] See also Fig. 9 a and Fig. 9 b. After 2000h of wet heat aging, the perovskite solar module containing 4-ABA maintained 100% of its initial efficiency; the perovskite solar module without 4-ABA only retained 70% of its initial efficiency. The above results confirm that the introduction of the 4-ABA crosslinker involved in the present invention can effectively improve the stability of PSMs, and a third-party stability certification report for the perovskite module (German Electrical Engineers Association 85℃ / 85%RH aging and light aging stability certification report) was obtained.
[0097] The above description is only by way of illustration of certain exemplary embodiments of the present invention. It is undoubted that those skilled in the art can modify the described embodiments in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A quasi-two-dimensional perovskite containing a double anchor crosslinker, characterized in that: The raw materials of the quasi-two-dimensional perovskite containing a double-anchor crosslinking agent include: a double-anchor crosslinking agent, a perovskite system and a precursor solution.
2. A quasi-two-dimensional perovskite containing a double anchor crosslinker according to claim 1, characterized in that: The double anchor crosslinking agent includes a combination of at least one crosslinking agent selected from 4-(aminomethyl)benzoic acid, 3-(aminomethyl)benzoic acid, 2-(aminomethyl)benzoic acid, 4-(aminomethyl)benzenesulfonic acid, 3-(aminomethyl)benzenesulfonic acid or 2-(aminomethyl)benzenesulfonic acid.
3. A quasi-two-dimensional perovskite containing a double anchor crosslinker according to claim 1, characterized in that: The perovskite system is BA2(FA 0.85 Cs 0.15 ) n-1 Pb n I 3n+1 (n = positive integer) or BA2FA n-1 Pb n I 3n+1 (n=positive integer).
4. The quasi-two-dimensional perovskite containing a double anchor crosslinker according to claim 1, characterized in that: The precursor solution is prepared by dissolving 1.0 mmol of the perovskite system in 1 ml of a mixed solvent system, and the mixing ratio of the mixed solvent system is DMF:NMP:2-Me=7:3-x:x (0≤x≤3).
5. A quasi-two-dimensional perovskite containing a double anchor crosslinker and a preparation method thereof according to claim 4, characterized in that: The content of the double anchor crosslinking agent is 1% to 4% by mole relative to the PbI2 in the precursor solution.
6. A method for preparing a quasi-two-dimensional perovskite containing a double anchor crosslinker, characterized in that: The steps include: A double anchor crosslinker is added to the precursor solution, and the mixture is mixed and stirred until fully dissolved to obtain a quasi-two-dimensional perovskite containing the double anchor crosslinker.
7. A perovskite solar module, characterized in that: The invention comprises a quasi-two-dimensional perovskite containing a double anchor crosslinker as described in any one of claims 1 to 5, and further comprises a transparent conductive oxide substrate, an inorganic p-type semiconductor hole transport layer, an electron transport layer, a barrier layer and an electrode layer, an organic encapsulation layer and a cover glass.
8. A perovskite solar module according to claim 7, characterized in that: The inorganic p-type semiconductor hole transport layer material is nickel oxide or metal-doped nickel oxide.
9. A perovskite solar module according to claim 7, characterized in that: The barrier layer is bathoxime BCP or tin oxide.
10. A perovskite solar module according to claim 7, characterized in that: The electrode layer is a metal electrode, and the metal electrode is a combination of at least one metal electrode selected from the group consisting of silver, gold, copper, bismuth, chromium, and nickel.
